The need to improve social work students' skills as future social policy actors: experiences and prospects in undergraduate training - Lluis Francesc Peris Cancio (Social Work & Society, 2022)
The article examines the field-based tools used to train future social workers and the way they help students mature through experiences of community contact as a key element in social policy formulation. Using a five-year study conducted at Sapienza University of Rome, it analyzes how students view these hands-on methodologies as enabling them to gain a greater understanding of course content, a broader appreciation of the discipline, and a greater sense of personal values and civic participation. The article also explores the relationship between training tools and students' professional growth by taking experience as a key element in constructing social policies and focusing on the outcomes that can be achieved through field-based activities. In addition to project-based learning, professional internships, and volunteer work, the article considers how incorporating service learning into degree courses could enhance and strengthen social worker training in social policy-making by potentially compensating for the limitations of existing learning methods.